T(t) = H(t) - H(t - 1) where H(t) is the Heaviside Step function: Heaviside step function - Wikipedia, the free encyclopedia
y'' + 2y' -35y = T(t)
Where T(t) =
1 from 0 to 1
0 from 1 to infinity
y'(0) = 0, y(0) = 0
part 1:
Y(s) = ?
After taking Laplace of both side I get
(s^2-2s-35)Y(s) = 1/s
Y(s) = (1/s)(1/(s^2-2s-35))
but it's wrong...
and second part
Find the inverse transform to find y(t)
How would I approach that?
Thank you!!!
T(t) = H(t) - H(t - 1) where H(t) is the Heaviside Step function: Heaviside step function - Wikipedia, the free encyclopedia